Рушник як символ у когнітивній моделі світу праукраїнців - Яковлєва, О. (Народна творчість та етнографія, 2006)
The article is about the meaning and the role of a towel as one of the most important subjects in the family traditions, connected with a birth of a child, wedding and funerals. In these customs the towel is viewed as a symbol, the meaning of which is analyzed from the point of view of the cognitive model of the world of our ancestors. Key words: mythological thinking, symbol as a real subject, action symbol, mandala, protective means.